Intelligent Visual Robot Navigator via Type-2 Fuzzy Logic and Horn-Schunck Methods - NADOUR, Mohamed; CHERROUN, Lakhmissi; BOUMEHRAZ, Mohamed (University of Eloued جامعة الوادي, 2022)
The aim of this paper is to propose a visual navigation control system for a wheeled mobile robot using a type-2 fuzzy logic controller (T2FLC) and Horn-Schunck algorithm (HS) of optical flow (OF) approach. The obstacle avoidance task for an autonomous mobile robot is studied using Takagi-Sugeno fuzzy logic controller based on video acquisition and image processing algorithm. The horn-Schunck algorithm is applied to extract information about the environment and estimate the positions of the surrounding obstacles. The captured image is divided into two parts right and left in order to facilitate the robot motion. Simulation is done using Visual Reality Toolbox in 2D and 3D. The obtained simulation results demonstrate the effectiveness of this autonomous visual navigator.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Horn-Schunck algorithm · Mobile Robot · type-2 fuzzy logic · VRML toolbox · visual navigation